Empirical studies of cloud computing in education: a systematic literature review - Sheikh Ibrahim, Mohamud; Salleh, Norsaremah; Misra, Sanjay (2015)
The purpose of this paper is to present the evidence about adoption of cloud computing in the education system in universities or higher education institutions. We performed a systematic literature review (SLR) of empirical studies that investigated the current level of adoption of cloud computing in the education systems and motivations for using cloud computing in the institution. Twenty-Seven papers were included in our synthesis of evidence. It has been found that several universities are interested in using cloud computing in their education systems, and they have utilized different types of cloud computing service models (IaaS, PaaS, SaaS). The results of this SLR show that a clear gap exists in this research field: a lack of empirical studies focusing on utilizing cloud computing within educational institutions.